Saline obtaining and time standardization of prothrombin using thromboplastin of human placenta. - María de Jesús Sánchez Bouza; Pedro Sánchez Frenes; Albert Vera Razumova; Miriam Soto González; Deysi González Sarría; Junior Jáuregui Solís (Medisur)
Background: Determining prothombine ‘s time is an important lab test in the study of coagulation disorders. To develop this essay the main reactive was thromboplastin , a substance that is presented in tissue and that has been obtained habitually from the human brain or certain animals but its extraction in labs or its commercial acquisition is difficult at present. Objective: To obtain Thromboplastin throughout the extraction of human placenta and to standardise the determination of pro-time into the obtained reactive Method: Placenta from normal delivery was used from which thromboplastin was obtained using a saline extraction. The reactive was compared with thromboplastin from human brain from ¨Dr. Hermanos Ameijeiras¨ Hospital in Havana City in a group of patients with and without anticoagulant treatment . With the extracted thromplastin similar or compatible results were obtained than with the habitual reactives by using easier and cheaper process.